How to catch a cricket ball. - Dienes, Z; McLeod, P (1993)
A cricket or baseball fielder can run so as to arrive at just the right place at just the right time to catch a ball. It is shown that if the fielder runs so that d2(tan alpha)/dt2 = 0, where alpha is the angle of elevation of gaze from fielder to ball, then the ball will generally be intercepted before it hits the ground. This is true whatever the aerodynamic drag experienced by the ball. The only exception is if the ball is not approaching the fielder before he starts to run.